View of the Mandapa of the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
View of the mandapa (pillared hall) of the Shiva temple from the northwestern side. To the western principal entrance of the temple, there is a mukhmandapa (front porch), which further connects to the mandapa. The mandapa is of a semi-open type, wherein the corner walls have peepal leaf motifs as surface decorations.